The Impact of Globalization on Corporate Culture and Communication - Khomenko, Y.V.; Khomenko, I.A.; Borodina, E.S. (Економічний вісник Донбасу, 2015)
In this paper some visible features and outcomes of globalization are regarded. The focus is mostly done on the European economic integration, progress in information and knowledge communication technologies and environmental challengers. In each case the peculiar characteristics of the process are distinguished, its influence on corporate culture and communication is determined and corporate reaction on these challengers is viewed.